1996
DOI: 10.1021/jo9600870
|View full text |Cite
|
Sign up to set email alerts
|

Single and Double Diastereoselection in Azomethine Ylide Cycloaddition Reactions with Unsaturated Chiral Bicyclic Lactams

Abstract: Double diastereoselectivity data were analyzed to provide insight into the structural features that influence π-facial selectivity in 1,3-dipolar cycloadditions of chiral and achiral azomethine ylides to chiral, unsaturated bicyclic lactams. Three major steric contributions to the differences in stability (ΔΔG ⧧) between competing cycloaddition transition states were identified. The first major set of steric interactions involve that between the dipoles and the substituents on the left hemisphere (R2) and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…264 Meyers et al have studied the addition of azomethine ylides 255 to chiral unsaturated bicyclic lactams 256 (eq 42). [268][269][270][271] The diastereoselectivities are dependent on the various substituents R 1 -R. 4 For R 1 ) Me, Ph, the major storeoisomer obtained is 257 (eq 42), whereas for R 1 ) H the other diastereomer is formed. 269 Furthermore, it was found that for R 3 ) H, the π-facial selectivity is insensitive to the chiral substituents of the dipole (R 4 ) chiral group), whereas for R 3 ) CO 2 Me or CO 2 t-Bu lower selectivities were observed.…”
Section: Chiral Alkenesmentioning
confidence: 99%
“…264 Meyers et al have studied the addition of azomethine ylides 255 to chiral unsaturated bicyclic lactams 256 (eq 42). [268][269][270][271] The diastereoselectivities are dependent on the various substituents R 1 -R. 4 For R 1 ) Me, Ph, the major storeoisomer obtained is 257 (eq 42), whereas for R 1 ) H the other diastereomer is formed. 269 Furthermore, it was found that for R 3 ) H, the π-facial selectivity is insensitive to the chiral substituents of the dipole (R 4 ) chiral group), whereas for R 3 ) CO 2 Me or CO 2 t-Bu lower selectivities were observed.…”
Section: Chiral Alkenesmentioning
confidence: 99%
“…From previous work dealing with the synthesis of chiral cyclopentenones and 3,4-disubstituted pyrrolidines derived from chiral bicyclic lactams, it was felt that a potentially efficient route to the tetracyclic ring system B of (+)-conessine could be accessed. Thus, a synthetic plan was devised (Scheme ) which would utilize a (3 + 2) azomethine ylide addition to the suitably substituted chiral, nonracemic lactam 7 .…”
Section: Introductionmentioning
confidence: 99%
“…61 A related bicyclic system has been investigated exhaustively by Meyers and co-workers, who have examined various types of ring manipulations to access a diversity of functionalised products. [62][63][64]…”
mentioning
confidence: 99%